Hematology and blood chemistry reference values of free‐ranging Callithrix geoffroyi in Urban environment in Espírito Santo state, Brazil. Issue 3 (21st February 2021) - Gariglio, Ana Clara R. S.; Boere, Vanner; Malukiewicz, Joanna; Abreu Fonseca, Leandro; Calais, Antonio; Silva, Ita Oliveira
Abstract: Background: The Callithrix geoffroyi are increasingly present in Brazilian urban areas, where they are vulnerable to health problems. The purpose of this study was a description of hematology and nine blood chemistry parameters of free‐ranging C .  geoffroyi . Methods: Thirty individuals were captured in urban‐forested settings. The marmosets were anesthetized, venopunctioned, and released shortly after recovery. The analysis was carried on in a veterinary laboratory, using automatic cells counter, staining methods, and an automatic biochemical analyzer. Results and Conclusions: Male and female free‐ranging C .  geoffroyi have similar hematological and blood chemistry values. The adults presented higher concentrations of erythrocytes ( P  <.02) and hemoglobin ( P  <.02) than young marmosets. The platelet concentration was lower ( P  <.05) in adults comparing to young marmosets. There were not statistically significant differences between young and adult blood chemistry concentrations. This is the first time that are presented hematology and blood biochemistry data on free‐ranging C .  geoffroyi .